Increasing Students’ Capabilities in Writing Simple Present Tense through Engklek Modification with CTL Approach - Febri Nurmala Dewi; Asri Wijiastuti (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
This research was motivated by the low ability of hearing impairment students in SLB Negeri I Gunungkidul in writing Simple Present Tense. Overcoming this problem, the Class Action Research (CAR) was done by using Engklek modification with CTL approach to increase the students’ ability in writing Simple Present Tense. This study was aimed at describing the improvement of the students’ ability in grade VII SLB Negeri 1 Gunungkidul in writing Simple Present Tense through Engklek modification with CTL approach. The method used was a Classroom Action Research with spiral model research design by Kemmis and McTaggart. This study was conducted in 2 cycles. Each cycle consists of stages: (1) planning, (2) implementation, (3) observation, and (4) reflection. The subjects were 4 students with hearing hearing of grade VII at SLB Negeri 1 Gunungkidul. It can be concluded that the learning of modification with CTL approach could increase students’ ability in writing Simple Present Tense. So, it is recommended that teachers should use a modified Engklek with CTL approach for writing Simple Present Tense.Penelitian ini dilatarbelakangi oleh rendahnya kemampuan siswa tunarungu di SLB Negeri 1 Gunungkidul dalam menulis simple present tense. Untuk mengatasi permaslahan ini, peneliti melakukan penelitian tindakan kelas dengan menggunakan engklek modifikasi dengan pendekatan CTL untuk meningkatakan kemampuan siswa dalam menulis simple present tense. Maka dari itu penelitian ini bertujuan untuk mendeskripsikan peningkatan kemampuan siswa kelas VII SLB Negeri 1 Gunungkidul dalam menulis simple present tense melalui engklek modifikasi dengan pendekatan CTL. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan kelas dengan desain penelitian model spiral oleh Kemmis and McTaggart. Penelitian ini dilaksanakan dalam 2 siklus. Tiap siklus terdiri atas tahapan: (1) perencanaan, (2) pelaksanaan, (3) observasi, dan (4) refleksi. Subjek penelitian ini adalah 4 siswa tunarungu kelas VII di SLB Negeri 1 Gunungkidul. Teknik pengumpulan data yang digunakan yaitu tes, observasi, dan dokumentasi. Dapat disimpulkan bahwa pembelajaran engklek modifikasi dengan pendekatan CTL dapat meningkatakan kemampuan siswa dalam menulis simple present tense. Sehingga disarankan agar guru menggunakan engklek modifikasi dengan pendekatan CTL untuk pembelajaran menulis simple present tense.